(untitled) (Research, Society and Development, 2019)
Current research has shown an interest in renewable alternatives to the contemporary primary source: oil. Biodiesel has been gaining increasing importance as an attractive fuel due to this depletion of fossil fuel resources, which in turn release greenhouse gases into the atmosphere. Thus, the objective of this work was to carry out a bibliometric review, involving the systems dynamics approach for biodiesel evaluation. A quantitative analysis of the articles found in the Web of Science database was carried out, followed by a qualitative analysis, examining the importance of the study of systems dynamics in the evaluation of the scenario for the study of policy and technological development renewable energy.